Microbiological quality assessment and acceptance of dairy products in Dhaka city - Hossain, Md Nur; Humayun, Sanjida; Haque, Md Zahurul; Ahmed, Monzur Morshed (Asian-Australasian Journal of Food Safety and Security, 2017)
This investigation was carried out to evaluate the microbiological quality of the processed dairy products including borhani, matha/labang, sweet & sour yoghurt. Dairy products are consumed as desert and popular enough among the people. 50 of the different dairy samples were collected from street vendor and also from some branded shop in Dhaka city. The microbiological quality of the samples were analyzed and monitored according to criteria in European Commission Recommendations 2004/24/EC and 2005/175/EC, BSTI and USPHS. All the dairy products had high microbial load ranged 5.90×105cfu/ml to 8.97×109 cfu/ml. Coliforms were found up to 109 dilutions in milk based drink products Borhani and Labang considered a serious threat to the public health. The mold contamination was much lower in Borhani and Labang compared to yoghurt 7.86×108cfu/ml. Approximately 17% dairy products were contaminated by Salmonella spp. Majority of the dairy products (25.537%,) such as Yogurt, Borhani and Labang were contaminated by Staphylococcus spp. The presence of Listeria monocytogenes found in Yogurt, 7 out of 21 (21.515%) samples were contaminated. A minor number of milk based products were corrupted by Shigella spp. These results emphasize applying and maintaining good hygiene practices throughout the processing chain to prevent contamination and bacterial growth. It was concluded that the presence of some pathogens in milk based products with toxigenicity of some strains pose a health hazard to consumers. Thus, good hygienic practices, good manufacturing practices, HACCP with all other hygienic practices should be applied during processing and distribution for public health safety. Asian Australas. J. Food Saf. Secur. 2017, 1 (1), 58-64